Maternal and infant characteristics influencing the anogenital distance and penile length in newborns - Singal, Arbinder Kumar; Jain, Viral G. (Andrologia, 2016)
Summary Recent studies have suggested that maternal characteristics can affect reproductive health of offspring, possibly through pre‐natal hormonal influence. Anogenital distance (AGD) is an anthropometric measure which is a sensitive reproductive endpoint of masculinisation. It provides a read‐out of pre‐natal androgen exposure and has been associated with several reproductive health outcomes in humans. We studied AGD and stretched penile length (SPL) in a large, racially homogenous sample of consecutive newborns to understand their association with maternal and infant characteristics. A prospective cross‐sectional study involving measurement of AGD and SPL at birth was performed by a single trained observer. A total of 1077 newborns (553 males and 524 females) were included in final anthropometric analysis. The mean AGD of males was 2.56 ± 0.31 cm, and the mean AGD of females was 1.54 ± 0.17 cm. The mean SPL of males was 3.31 ± 0.38 cm. On multiple regression analysis, for both males and females, birthweight (β = 0.229, P < 0.001 and β = 0.135, P < 0.001, respectively) was modest but significant predictor for AGD. For SPL, only gestational age (β = 0.054, P < 0.001) was found to be statistically significant predictor. There was no significant association observed for gravidity, parity and maternal age with both AGD and SPL. Thus, no maternal characteristics (age, gravidity, parity) influence AGD or SPL in human infants.